ASEAN-5 Economic Analysis Based on Financial Inclusion and Financial Technology - Lia Nazliana Nasution; Rusiadi Rusiadi; Diwayana Putri Nasution (DPPM Universitas Pelita Bangsa, 2023)
This research aims to find leading economic indicators in each ASEAN-5 country based on financial inclusion and FinTech. Five ASEAN developing countries, Indonesia, the Philippines, Vietnam, Malaysia, and Thailand, were used as observations from 2009 to 2019. The analysis method of this study used the ARDL Panel approach. The results obtained from the ARDL Panel model are: (1) Leading economic fundamental indicators of unemployment rates in Indonesia, the Philippines, Vietnam, Malaysia, and Thailand are through the variable number of bank branches, savings, and e-money (2) Leading indicators of economic fundamentals Inflation rates in Indonesia, the Philippines, Vietnam, and Malaysia are through savings and e-money variables (3) Thailand is the chosen country because the three observation variables, namely the number of bank branch offices, savings, and e-money, can become leading indicators of economic fundamentals for controlling inflation rates.